PERNIKAHAN DINI DAN LAMBAT: MERAMPAS HAK-HAK ANAK - Moh. Roqib (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
marrying the child in time means respecting the rights of children, propose marriage at an early age children will take thechildren to play and study time at the same time not giving a chance for children to prepare themselves to be truly ready and mature.Likewise, if a delay marriage will cause problems for the rights of the child for the two brides who marry late because he'll also have kids whoneed attention and education. If he was old and weak, then the efforts become less maximal. Preparation for marriage levels are important.Preparation steady without doubts and fears that Muslim youth are ready and have been married at the right time is not too early and nottoo late.